Recommended operating room practice during the COVID‐19 pandemic: systematic review. Issue 5 (4th June 2020) - ,
Abstract : Background: The COVID‐19 pandemic poses a critical global public health crisis. Operating room (OR) best practice in this crisis is poorly defined. This systematic review was performed to identify contemporary evidence relating to OR practice in the context of COVID‐19. Methods: MEDLINE was searched systematically using PubMed (search date 19 March 2020) for relevant studies in accordance with PRISMA guidelines. Documented practices and guidance were assessed to determine Oxford Centre for Evidence‐Based Medicine (OCEBM) levels of evidence, and recommendations for practice within five domains were extracted: physical OR, personnel, patient, procedure, and other factors. Results: Thirty‐five articles were identified, of which 11 met eligibility criteria. Nine articles constituted expert opinion and two were retrospective studies. All articles originated from the Far East (China, 9; Singapore, 2); eight of the articles concerned general surgery. Common themes were identified within each domain, but all recommendations were based on low levels of evidence (median OCEBM level 5 (range 4–5)). The highest number of overlapping recommendations related to physical OR (8 articles) and procedural factors (13). Although few recommendations related to personnel factors, consensus was high in this domain, with all studies mandating the use of personal protective equipment. Conclusion: There was little evidence to inform this systematic review, but there was consensus regarding many aspects of OR practice. Within the context of a rapidly evolving pandemic, timely amalgamation of global practice and experiences is needed to inform best practice. Abstract : This rapid systematic review was performed to identify contemporary evidence relating to operating room (OR) practice during the COVID‐19 pandemic. Evidence underpinning the review was sparse; however, consensus regarding many aspects of OR practice was apparent. High quality evidence needed Abstract : Antecedentes: La pandemia por COVID‐19 plantea una crisis crítica de salud pública a nivel mundial. La mejor práctica en el quirófano en esta crisis está mal definida. Esta revisión sistemática se realizó para identificar la evidencia contemporánea relacionada con la práctica en el quirófano en el contexto del COVID‐19. Métodos: Se realizó una búsqueda sistemática en Medline usando PubMed (fecha de búsqueda, 19 de marzo de 2020) para seleccionar estudios relevantes de acuerdo con las directrices PRISMA. Las prácticas documentadas y las guías se evaluaron para determinar los niveles de evidencia según la normativa Oxford (Oxford levels of evidence, OLE), y se extrajeron las recomendaciones para la práctica en el entorno de cinco ámbitos: físico en el quirófano, personal, paciente, procedimiento y otros factores. Resultados: Se identificaron 35 artículos, de los cuales 11 cumplían con los criterios de elegibilidad. Nueve artículos constituían opinión de expertos y dos fueron estudios retrospectivos. Todos los artículos provenían del Lejano Oriente (nueve de China, dos de Singapur); ocho de los artículos estaban relacionados con cirugía general. Se identificaron temas comunes en cada ámbito, pero todas las recomendaciones se basaron en bajos niveles de evidencia, mediana de 5 OLE (rango 4 ‐ 5). El mayor número de recomendaciones superpuestas se relacionaban con el ámbito físico del quirófano ( n = 8) y con factores del procedimiento ( n = 13). Aunque hay pocas recomendaciones relacionadas con factores del personal, el consenso fue alto en este ámbito, y todos los estudios exigieron el uso de equipos de protección personal. Conclusión: Hubo poca evidencia para que esta revisión sistemática proporcionara información, pero existió consenso con respecto a muchos aspectos de la práctica en el quirófano. En el contexto de una pandemia en rápida evolución, es preciso aglutinar a tiempo real las estrategias y experiencias globales a fin de poder informar acerca de las mejores prácticas.